BizComp social networking site for business computing / Raina Kariena Mohamad Halim Shah - Mohamad Halim Shah, Raina Kariena (2012)
Social networking sites are becoming essential in a person's life. The feature it provides completes a way of communication among each other. As of students, majority it's becoming trend to daily updates their current event. In Business Computing program, news, events or updates are passed through words of mouth, poster, banner, etc. Therefore, in order to unite all medium of communication, BizComp is designed. It fits a persons' interest onhaving a social network sites being applied in their educational updates as it is able to exchange information effectively. The fact that this platform allows combination of other communication medium gives variety and benefits over one single medium of communication.